Pengaruh Sosialisasi Self-Healing Dengan Mindful Cooking Terhadap Tingkat Penurunan Kecemasan Mahasiswa Universitas Nurul Hasanah Kutacane - Siska Putri Belangi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Self-healing is intended as a process of treatment or healing that is carried out by oneself through the process of one's own beliefs and is also supported by the environment and external factors. This research aims to analyze the effect of self-healing socialization with mindful cooking on reducing anxiety levels for students at Nurul Hasanah University, Kutacane. The research design used in this research is a quasi-experimental method. The design used is a group pre-test and post-test design. The sample in this study involved one group of subjects. This research reveals a cause-and-effect relationship by involving one group of subjects. The research was carried out on 16 December 2023-16 January 2024. This research examines the variable self-healing with mindful cooking and reducing anxiety levels. There is an influence of socialization counseling on the level of anxiety reduction, the significance value is p-value 0.000 <???? = 0.05 (5%) with a t count of -9.420. There is a significant difference in knowledge and attitudes regarding reproductive health nutrition between the pretest and posttest, indicating that there is an influence on reduced level of anxiety.